MENINGKATKAN PRESTASI BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL COOPERATIF LEARNING INVESTIGASI KELOMPOK KELAS I SD - .SUTANI (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2013)
The problems to be examined in this study is an increase in student achievement in cooperative learning model Learning Methods Investigation Group on Student Class I includes procedures Implementation of action plan , action, observation and reflection . Classroom action research was conducted in three cycles . TOD : .The data collection technique is the technique of observation and evaluation at the end of each lesson . The subjects were students of class I SD SSN East Cengkareng , West Jakarta 07 Morning totaling 30 students . observations using the observation sheet that the information obtained in the learning activities of students has increased each cycle , it can be seen from the average value of learning activities in each cycle , namely the pre-cycle average of 54.6 , an average first cycle 74.7 , the cycle II 82 , and the third cycle was 84 . 3 . Investigating the application of learning methods to improve the learning outcomes of group operations of addition and subtraction of numbers . This can be seen from the graph the increase in the average test score of students before and after the use of Group Investigation method to an increase of each cycle , the pre-cycle , shows the average results of individual test is 49 , the first cycle shows the average results of individual tests is 57.Sedangkan on the second cycle showed an increase in the value of 75 , and the third cycle reaches 84.33 . KKM when determined by the school is 70 .Based on the research results , it was concluded that the application of this approach to learning can develop a way of thinking , creativity , mathematics achievement